PENCIPTAAN DESTINATION BRANDING KAWASAN WISATA B-29 KABUPATEN LUMAJANG SEBAGAI UPAYA MEMPERKENALKAN OBYEK WISATA BARU - Abdullah, Ali; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: design creation of Destination Branding tourist area B-29 is promotional efforts, provide information about natural attractions inside are cultures that can be preserved and can become one of the new tourist attractions in Indonesia The study was conducted using qualitative methods is by doing interviews, observation ,documentation, and literature to obtain data used as drafting the manufacture of Destination Branding. Concept or keyword obtained through data analysis, keyword analysis performed Based on the acquired keyword is